Identification of Peat Land Pollution in Sungai Terap Village Using Wenner Configuration Geoelectric Method - Ira Kusuma Dewi; Nasri MZ; Ichy Lucya Resta; Juventa Juventa (xxxx-xxxx, 2020)
Dewi IK, MZ Nasri, Resta IL, Juventa J.2020. Identification of Peat Land Pollution in Sungai Terap Village Using Wenner Configuration Geoelectric Method. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang  20 Oktober 2020. pp. xxx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Groundwater pollution arising from the conversion of functions on peatlands in Sungai Terap Village. To identify the ground air pollution, the geoelectric method of research using Wenner was carried out. This research was conducted in 4 tracks with a length of 200 meters and the distance between the electrodes was 10 meters with 4 times the electrode spacing. The results of this study are 2D subsurface models in the form of apparent resistivity from the inversion results. The resistivity value generated in the 2D model ranges from 0.381-19 Ωm. The water content at the research location with a very small resistance value between 0.4-1.25 Ωm. The presence of groundwater is estimated to be trapped in the alluvium layer at a depth of 7.75-19.4 meters. The groundwater is thought to have been polluted because it has a resistivity value <10 Ωm. Almost every measurement path is found in polluted air due to rainfall and sea water intrusion.